Restore the Actant in the Socio-Ecological Sustainability Debate: A Case Study of the Ekowisata Mangrove Hijau Daun CSR Program - Budi, Eka Setia; Luqmania, Dewi; Sunani, Anjumiz (Global Writing Academica Researching and Publishing, 2023)
Natural activities are considered the primary cause of environmental damage that occurs in various locations. However, in reality, humans also contribute to environmental degradation, leading to climate change. Erosion and flooding disasters in the coastal areas of Daun Village do not solely occur due to the intrusion of seawater but also due to the behaviors of people who harm nature by engaging in mangrove deforestation and the use of chemicals by fishermen. This study aimed to highlight the Hijau Daun Mangrove Ecotourism Program as a best practice in conservation practices, serving as a significant consideration for the sustainability of human (actor) and non-human (actant) agencies in the future of Bawean Island. The method employed was a case study with a single-case study design and secondary data analysis, where the unit of analysis is the CSR Program of PT PLN Nusantara Power UP Gresik. The Hijau Daun Mangrove Ecotourism Program successfully addresses the issues caused by natural disasters and the activities of the local community that exacerbate their impact. Together with the Hijau Daun Community Monitoring Group (Pokmaswas Hijau Daun), CSR PT PLN Nusantara Power UP Gresik has been able to restore land, subsequently utilized for mangrove ecotourism, shrimp and crab aquaculture, agricultural land, and mangrove product processing. The restored mangrove forest provides more benefits to the people of Daun Village through the development of integrated programs. The goal of program implementation is not only to preserve the existence of the mangrove ecosystem as an actant but also to create reciprocity from environmental conservation activities for the future existence of humans (actors). The presence of volunteer movements in the community, such as Coastal Warriors, can help achieve the goals of the program.